Development of External Stimuli-Responsive Nucleic Acids by Sugar, Backbone, and Nucleobase Modification - Morihiro, Kunihiko; Kodama, Tetsuya; Obika, Satoshi (Synlett, 2014)
Nucleic acids are the principal materials for the preservation and flow of genetic information. The control of the properties of nucleic acids by using external stimuli is important for regulating biological processes and for the possibility of developing unique molecular machines. This account summarizes the development of external stimuli-responsive nucleic acids by our group. Our external stimuli-responsive nucleic acids are designed and synthesized through sugar, backbone, and nucleobase modifications. Various external stimuli, such as light, acids, or oxidants/reductants can trigger changes in nucleic acid structure. By means of such structural alterations, various properties of nucleic acid, including their hybridization ability, nuclease resistance, backbone degradability, and base-recognition ability, can be changed.1 Introduction2 External Stimuli-Responsive Nucleic Acids2.1 2′,4′-Bridged Nucleic Acid Analogues Bearing External Stimuli-Responsive Bridged Moieties2.2 Oligonucleotides Containing a P–N Phosphoramidite Linkage for Double-Stranded DNA-Templated Digestion2.3 Light-Triggered Change in the Hydrogen-Bonding Pattern of a Nucleobase Analogue Enables a Strand-Exchange Reaction3 Conclusions
Keywords: base recognition; external stimuli; hybridization; nuclease resistance; nucleic acids